PENERAPAN MODEL PEMBELAJARAN VAK (VISUALIZATION, AUDITORY, DAN KINESTETHIC) TERHADAP HASIL BELAJAR IPA PESERTA DIDIK KELAS IV SD NEGERI 147 PEKANBARU - Triyan Desti Elisa; Neni Hermita; Eddy Noviana (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
This research is motivated by the low involvement of students in learning. This study aims to determine the differences in the learning outcomes of science students between the experimental class and the control class by applying the learning model VAK. This study uses quasi-experimental methods with a nonequivalent control group design. This research was conducted in 147 Public Elementary Schools Pekanbaru with class IV D as the experimental class and class IV A as the control class. Based on the results of the study, it can be seen from the experimental class pretest score of 51.25 and posttest which is 80.63. In the control class the average score of the pretest was 45.53 and posttest was 72.89.The score of the average gain of experimental class science learning outcomes is 0.62 and the average score of the control class is 0.50. The results of the t-test gain score average thitung >  ttabel or 2,89966 > 1,99547 then Ha is accepted. Based on the results of the t gain test between the experimental class and the control class there were differences in learning outcomes IPA student learning in class IVSD Negeri 147 Pekanbaru which are significant.